Exercises for students of different medical groups as factors of the weakening bad habits at students - I. E. Kramida (Physical Education of Students)
The changes in the prevalence and strength of dependence on smoking and alcohol are studied. A comparative analysis of the strength of dependence on smoking and alcohol use among students attending classroom and those who were taught extracurricular. Experimenting In 1200 students participated. Research methods were estimated survey methods and mathematical processing of the survey, as well as methods of statistics. The results of the survey of more than 1226 students. It is proved that the contents should the physical training necessary to introduce elements that reduce the prevalence of these bad habits among students. It is shown that training health workshops are more effective than the physical training for the relatively healthy students.